A cognitive health test for fifth and sixth grade pupils, U.P. Integrated School - Matta, Lerma Saddul 1937-
This study was concerned with the development and construction of a valid and reliable cognitive health test for the fifth and sixth grade of the UP Integrated School. The statistical validity of the test was determined through item analysis, identification and revision, and determination of the reliability using the Kuder-Richardson Formula 20.